Effects of different rest intervals between antagonist paired sets on repetition performance and muscle activation - Maia, M. F.; Willardson, J. M.; Paz, G. A.; Miranda, H. (The Journal of Strength and Conditioning Research, 2014)
Recent evidence suggests that exercising the antagonist musculature acutely enhances subsequent performance for the agonist musculature. The purpose of this study was to examine the effects of different rest intervals between sets for exercises that involve antagonistic muscle groups, a technique referred to as antagonist paired sets (APS). Fifteen recreationally trained men were tested for knee extension (KE) exercise performance, with or without previous knee flexion (KF) exercise for the antagonist musculature. The following protocols were performed in random order with 10 repetition maximum loads for the KF and KE exercises: (a) traditional protocol (TP)—1 set of KE only to repetition failure; (b) paired sets with minimal allowable rest (PMR)—1 set of KF followed immediately by a set of KE; (c) P30—30-second rest between paired sets of KF and KE; (d) P1—1-minute rest between paired sets; (e) P3—3-minute rest between paired sets; and (f) P5—5-minute rest between paired sets. The number of repetitions performed and electromyographic (EMG) activity of vastus lateralis, vastus medialis (VM), and rectus femoris (RF) muscles were recorded during the KE set in each protocol. It was demonstrated that significantly greater KE repetitions were completed during the PMR, P30, and P1 protocols vs. the TP protocol. Significantly greater EMG activity was demonstrated for the RF muscle during the KE exercise in the PMR and P30 vs. the TP, P3, and P5, respectively. In addition, significantly greater EMG activity was demonstrated for the VM muscle during the PMR vs. all other protocols. The results of this study indicate that no rest or relatively shorter rest intervals (30 seconds and 1 minute) between APS might be more effective to elicit greater agonist repetition enhancement and muscle activation.